Globalisasi Budaya Musik Dangdut Koplo Melalui Media Tiktok (Pendekatan Komunikasi Lintas Budaya) - Kiram, Saiful (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
Dangdut music is no longer a local and ancient culture but has become a global or international culture. This is because dangdut music has now become one of the popular cultures in the current millennial era and has been introduced to foreign countries by Indonesian youths. Music sociologist Prof. Andrew N. Weintarub also added that dangdut music is an original culture from Indonesia, not from other countries and has been found in various regions and has been well received by all groups as well as being a unifier. This study aims to describe and analyze the phenomenon of Dangdut Koplo Music Culture on Tiktok Media, especially in the account posts belonging to the boyband